Women, music, culture : an introduction - Dunbar, Julie C. (New York : Routledge, 2021)
"Women, Music, Culture: An Introduction, Third Edition is the first undergraduate textbook on the history and contributions of women in a variety of musical genres and professions, ideal for students in Music and Gender Studies courses. A compelling narrative, accompanied by 112 guided listening experiences, brings the world of women in music to life. The author employs a wide array of pedagogical aides, including a running glossary and a comprehensive companion website with links to Spotify playlists and supplementary videos for each chapter. The musical work of women throughout history-including that of composers, performers, conductors, technicians, and music industry personnel-is presented using both art music and popular music examples"--
Telling musical stories : missing voices in the documentation of musical traditions. Reflections on "deep listening" : exploring music in context ; Medieval liturgical roots and the documentation of the Western canon ; Women in "world" music : an expanded view of global narratives -- Restricted domains : gender spheres in art music. Court performers of Japan, India, and Europe : freedom and restriction ; Baroque keyboard and vocal genres : gender roles in musical families ; Eighteenth-century Classicism : revisiting Vienna ; Romantic-era performer/composers : walking the public/private line -- Visual images in an aural world. American popular music : 1895-1945 ; Empowered voices in the public eye : women of gospel and blues ; Visual media and the marketing of women performers -- A time of change : the impact of education on women's art music activity. Changing gender roles : from nineteenth-century opera to the modern musical ; Segregation and integration : instrumental ensembles from 1900 to the present ; Large-scale works and experimental voices -- No longer "one of the boys". Instrumental to jazz : the forgotten role of women ; Technology in the hands of women: art music, multimedia, and popular music ; Popular music as a feminist platform : women in charge of production and management.
Includes bibliographical references and index.
Keywords: Women musicians; Feminism and music; Gender identity in music; Women composers; Music -- Social aspects; Music by women composers -- History and criticism